STUDI KUALITATIF DESK COLLECTION PADA PERUSAHAAN AGENT AND ANCO - Tuto, Maria Goreti; Kuswantoro, Ferri; Harnaji, Bimo (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
Research on desk collection and employee performance is a step taken to analyze and find problems that occur and to find solutions to the problems faced. This is a series of processes to determine and obtain effective model formulas that can be applied to Agent&Anco company employees in handling customers. and to improve the performance of company employees. This study used a descriptive qualitative method. The participants in this research were employees of the desk collection division at the Agent&Anco Company Yogyakarta. This research used interviews, observation, documentation and literature study as data collection techniques. From the results of research that had been carried out, the work model had been running well. This could be seen from the increase in the smoothness of installments in the last two  years at the Agent&Anco Company and of course, this could also be achieved because it was supported by good procedure operation standards, efficient and effective methods.